Observing attitudes, intentions and expectations (1945-1973) - José M. Edwards (Duke University, Center for the History of Political Economy (CHOPE), 2011)
Although involved in projects of influent institutions like the Cowles Commission, the NBER, and the Michigan Survey Research Center (SRC), George Katona, the "pioneer student and chief collector of consumer anticipations data" (Tobin, 1959, p. 1) is virtually absent from accounts of the topics he explored, including the study of the consumption function and the development of behavioral economics. This essay argues that such an absence is partly explained by the theoretical underpinnings of Katona's project, which were incompatible with the economic views of behavior that dominated from the mid-1940s to the mid-1970s. It compares alternative survey programs funded by the Federal Reserve during that period, and analyzes the ensuing controversy on the purposes of the observation of attitudes, intentions and expectations. It claims that understanding Katona's approach "required a real restructuring of thought - a genuine paradigm shift" (Simon, 1979, p. 12), which gives specific interest to this historical episode.
Keywords: B23; B31; B41; 330; George Katona; Michigan Survey Research Center; Subjective Data; Behavioral Economics